Analysis of cognitive status in patients with type 2 diabetes - Irina V. Gatckikh (Endocrinology Research Centre, 2017)
Background: Cognitive impairment is a common complication of type 2 diabetes, greatly reduce the quality of life and daily functioning of patients, as well as have an impact on their compliance to therapy. Aim: Explore the nature and frequency of cognitive impairment in patients with type 2 diabetes, their relation to carbohydrate metabolism. Materials and methods: The study involved 113 patients with type 2 diabetes aged 40–70 years, with disease duration of more than 12 months; Control group consisted of 33 persons, stateless persons with type 2 diabetes, matched by age, sex, level of education, the presence of cardiovascular diseases such as hypertension and coronary heart disease. The complex included a survey of clinical and laboratory tests, instrumental, neuropsychological testing. To screen for cognitive impairment used by the Montreal Cognitive Assessment Scale (MоСа test), for the study of the frontal functions FAB (frontal dysfunction battery). Results: The study of cognitive impairment were diagnosed in 53,1 ± 9,2% of patients with type 2 diabetes, which is statistically significantly higher than in those in the control group 15,2 ± 12,2%. In patients with type 2 diabetes prevailed violations fronto-subcortical type with a reduction in short-term memory function, attention and constructive praxis. Cognitive impairment correlated with indices of carbohydrate metabolism (HbA1c, fasting glucose), disease duration 7 [5, 12] years and the patient's. Conclusions: These data confirm the impact of hyperglycemia as a major pathogenic factor and duration of the disease on the formation and progression of cognitive impairment in patients with type 2 diabetes.